Salinity of the agricultural soils in some farms due to the long-term sprinkling irrigation, ALDABWAT agricultural project - Iessa, Kaes Rateb (JATAED: Journal of Appropriate Technology for Agriculture, Environment, and Development, 2024)
The quality of irrigation water available to irrigators significantly impacts crops and yields. Therefore, there is a need to understand irrigation water quality better. The present study mainly focuses on assessing the suitability of water in five bore wells of the Aldabwat agriculture project in Alshatti, Libya. The well water samples were evaluated for agricultural uses according to the universal standard classification. Separate bore wells have been analyzed for various water quality indices, including exchangeable sodium percent (SSP or %Na), residual sodium carbonate (RSC or RA), Kelly’s ratio, permeability index, potential salinity (PS), magnesium hazard, total dissolved solids, and total hardness. Most of the wells fall under the moderate water category for irrigation purposes. The analysed water was specified as having a low restriction according to the water quality index (IWQ index).